2015
DOI: 10.3944/aott.2015.14.0250
|View full text |Cite
|
Sign up to set email alerts
|

Radiation in the Orthopaedic Operating Theatre

Abstract: The rate of radiation determined in the dosimeters decreased when distance from the radiation source increased. During the use of fluoroscopy in orthopedic surgery, the wearing of lead aprons, neck protectors, and glasses, in addition to maintaining a distance from the tube, will reduce the radiation exposure of individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…In a study conducted by Ismail and his colleagues, 11 resident doctors were most exposed to radiation in the operating room, while orthopedic and urologic specialists were second. Again, in a study conducted in Turkey, the amount of radiation in the region where orthopaedic surgeons worked was found to be higher than the amount of radiation in the area where the anesthetist worked 12 . But our study has shown that orthopedic surgeons do not adequately comply with the methods of protection.…”
Section: Discussioncontrasting
confidence: 75%
“…In a study conducted by Ismail and his colleagues, 11 resident doctors were most exposed to radiation in the operating room, while orthopedic and urologic specialists were second. Again, in a study conducted in Turkey, the amount of radiation in the region where orthopaedic surgeons worked was found to be higher than the amount of radiation in the area where the anesthetist worked 12 . But our study has shown that orthopedic surgeons do not adequately comply with the methods of protection.…”
Section: Discussioncontrasting
confidence: 75%
“…Numerous studies have been conducted on radiation dosage calculation [17][18][19][20][21][22][23][24][25]. There are studies that determine the amount of radiation to which hospital personnel are exposed during surgeries in which fluoroscopy is actively used [26] or the radiation value to which the patient's oral mucosa is exposed during CT [27]. However, there is no study in the literature that determines the amount of radiation to which patients' oral cavity is exposed during fluoroscopy imaging.…”
Section: Evaluation Of Radiation Exposure Of the Oral Cavity In C-arm...mentioning
confidence: 99%